ANALISIS PERKEMBANGAN PSIKOSOSIAL PADA ANAK USIA DINI DITINJAU BERDASARKAN POLA ASUH ORANG TUA DI KECAMATAN PURWAKARTA - Fatika Hilma Ashyla; Jojor Renta Maranatha; Idat Muqodas (UNIB Press, 2023)
Parenting styles can influence children's psychosocial developmental disorders. The purpose of this study is to examine children's psychosocial development in relation to parenting style. This study employs a descriptive-qualitative approach, with data gathered via questionnaires and interviews. The study included nine parents who had children aged 5 to 6 years old and had varying parenting styles. The research findings were analyzed using an interpretive research coding data analysis approach. According to the study's findings, democratic parenting promotes psychosocial development in early childhood by achieving eight indicators of psychosocial development. Whereas psychosocial development with permissive parenting patterns results in children feeling guilty, authoritarian development results in children who cannot trust, are less enthusiastic, lack self-identity, and lack self-confidence. As a result, it is possible to conclude that psychosocial development in early childhood is best achieved through democratic parenting.